Frequency of Breast Cancer Recurrence and Factors Impacting the Recurrence and Survival - Ayesha Inam, Sikandar Iqbal, Muhammad Zafar, Fazli Akbar, Samina Ashfaq, Fozia Shaikh, Saadia Muhammad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast cancer recurrence remains a critical challenge despite advancements in screening and treatment. Identifying factors influencing recurrence and survival is essential to improving outcomes. Objective: To determine the frequency of breast cancer recurrence, assess factors impacting recurrence, and evaluate survival outcomes. Material and Methods: This retrospective study included 282 breast cancer patients treated between January 2022 and December 2022 at the Hayatabad Medical Complex Peshawar. Demographic, clinical, and tumor-related variables were analyzed using descriptive statistics. Associations between recurrence status and variables were evaluated using the chi-square test, and survival outcomes were assessed. A p-value ≤ 0.05 was considered statistically significant. Results: The mean age of the patients was 49.00 ± 14.83 years, with a mean BMI of 27.66 ± 3.79 and a mean tumor size of 2.91 ± 1.16 cm. The recurrence rate was 29.1%, with 200 (70.9%) patients experiencing no recurrence and 82 (29.1%) having recurrence. Overall survival was 79.1%, with 223 patients alive and 59 deceased. Hormone receptor-negative tumors were significantly associated with recurrence (p = 0.010). Smoking status showed borderline significance (p = 0.052), while HER2 status, tumor stage, and lymph node involvement did not demonstrate significant associations with recurrence. Conclusion: The study highlights the persistent burden of breast cancer recurrence and its impact on survival. Hormone receptor-negative tumors and modifiable factors like smoking are critical in recurrence risk, underscoring the need for stratified management and lifestyle interventions to improve long-term outcomes. Keywords: Breast cancer, recurrence, survival, hormone receptor status, risk factors, smoking.